Morrey spaces : introduction and applications to integral operators and PDE's. Volume II - Sawano, Yoshihiro; Di Fazio, Giuseppe, 1963-; Hakim, Denny Ivanal (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
Morrey spaces were introduced by Charles Morrey to investigate the local behaviour of solutions to second order elliptic partial di?erential equations. The technique is very useful in many areas in mathematics, in particular in harmonic analysis, potential theory, partial di?erential equations and mathematical physics. Across two volumes, the authors of Morrey Spaces: Introduction and Applications to Integral Operators and PDE's discuss the current state of art and perspectives of developments of this theory of Morrey spaces, with the emphasis in Volume II focused mainly generalizations and interpolation of Morrey spaces. Features Provides a 'from-scratch' overview of the topic readable by anyone with an understanding of integration theory Suitable for graduate students, masters course students, and researchers in PDE's or Geometry Replete with exercises and examples to aid the reader's understanding
11. Multilinear operators and Morrey spaces. 12. Generalized Morrey/Morrey-Campanato spaces. 13. Generalized Orlicz-Morrey spaces. 14. Morrey spaces over metric measure spaces. 15. Weighted Morrey spaces. 16. Morrey-type spaces. 17. Pointwise product. 18. Real interpolation of Morrey spaces. 19. Complex interpolation of Morrey spaces. Bibliography. Index.
"A Chapman & Hall book."
OCLC-licensed vendor bibliographic record.
Keywords: MATHEMATICS / General; MATHEMATICS / Differential Equations; MATHEMATICS / Functional Analysis; Banach spaces; Harmonic analysis; Differential equations, Partial -- Numerical solutions; Differential equations, Elliptic -- Numerical solutions; Integral operators